Sitangkai Community Resources which can be utilized in teaching first year social studies in the Mindanao State University Community High School - Harun, Mona Gayon 1950- (1977)
The aims of the study were to make a survey of educational materials in Tawi-tawi that can be used in social studies teaching, and to illustrate how these materials can be used in actual teaching. The study presented a cross-sectional picture of the resources of Sitangkai, Tawi-Tawi which were classified as natural, human and man-made. The data in this study were made possible through the use of the following research instruments: documentary analysis, participant-observation and interview.
Vita.
Thesis (M.A. Social Studies Education)--University of the Philippines, Diliman.
Keywords: Social sciences -- Study and teaching (Secondary) -- Philippines -- Tawi-Tawi.; Teaching -- Philippines -- Tawi-Tawi -- Aids and devices